Identification and characterization of nanobodies specifically against African swine fever virus major capsid protein p72 - Yang, Jifei; Jing, Mengyao; Niu, Qingli; Wang, Jinming; Zhao, Yaru; Liu, Meng; Guan, Guiquan; Luo, Jianxun; Yin, Hong; Liu, Zhijie (Frontiers in Microbiology, 2022)
African swine fever virus (ASFV) is a large and very complex DNA virus. The major capsid protein p72 is the most predominant structural protein and constitutes the outmost icosahedral capsid of the virion. In the present study, the nanobodies against ASFV p72 protein were screened from a camelid immune VHH library by phage display technique. Nine distinct nanobodies were identified according to the amino acid sequences of the complementary determining regions (CDRs), and contain typical amino acid substitutions in the framework region 2 (FR2). Six nanobodies were successfully expressed in E. coli, and their specificity and affinity to p72 protein were further evaluated. The results showed that nanobodies Nb25 had the best affinity to both recombinant and native p72 protein of ASFV. The Nb25 possesses an extremely long CDR3 with 23 amino acids compared with other nanobodies, which may allow this nanobody to access the hidden epitopes of target antigen. Furthermore, the Nb25 can specifically recognize the virus particles captured by polyclonal antibody against ASFV in a sandwich immunoassay, and its application as a biosensor to target virus in PAM cells was verified by an immunofluorescence assay. Nanobodies have been proven to possess many favorable properties with small size, high affinity and specificity, easier to produce, low costs and deep tissue penetration that make them suitable for various biotechnological applications. These findings suggest that nanobody Nb25 identified herein could be a valuable alternative tool and has potential applications in diagnostic and basic research on ASFV.